WHY AUTOCRACIES SHUT DOWN NGOS: A CASE STUDY OF NEMOLCHI - Zamanbekova, Altynay (Nazarbayev University School of Sciences and Humanities, 2025)
This thesis analyses the relationship between the Kazakhstani state and NeMolchi, an influential NGO that advocates against gender-based violence and challenges official narratives. Drawing on legitimacy theory and using process tracing, the research tests two core hypotheses: (1) that the state represses NeMolchi to defend its domestic legitimacy when the NGO exposes governance failures, and (2) that international visibility of NeMolchi’s work increases repression as the state seeks to protect its international image. Empirical analysis of media reports, official documents, and public records found some supportive evidence to the first hypothesis. State responses including legal harassment, disinformation campaigns, and administrative pressure consistently followed moments when NeMolchi publicly revealed institutional failures or achieved advocacy successes. The second hypothesis received limited supporting evidence, while international recognition of NeMolchi and its founder, Dina Smailova, led to intensified scrutiny, the evidence was less consistent and lacked direct state attribution. The study also evaluates alternative explanations such as routine oversight and elite competition, finding them less persuasive considering the targeted and timely nature of state actions. This research contributes to the literature on civil society and authoritarianism by showing how gender-based activism, even when not overtly political, threatens regime legitimacy. It underscores the importance of legitimacybased repression in non-democracies and highlights the risks faced by NGOs addressing sensitive social issues.
АВТОРИТАРЛЫ РЕЖИМДЕРДЕГІ ҮЕҰ-ҒА ҚЫСЫМ: «НЕМОЛЧИ» ҰЙЫМЫ
Keywords: Civil society; Kazakhstan; Non-governmental organizations; State repression; type of access: embargo